(untitled) (Advancements in Homeopathic Research, 2022)
At present our MATERIA MEDICA of Homoeopathy is a “Mixed Bag” of signs and symptoms of drugs / medicines. We have in it - wanted and unwanted symptoms and signs. What we need is “what is curative in medicines?” for “what is curable in diseases (6, para. 3)?” which is not there. It contains proved, unproved, assumative, unauthenticated, unverified, imaginative, speculative, figurative, picturised, hypothetical, false conjectures and fictions, mis-interpreted, hallucinative, illusionary, delusionary, dreamy, abstract, pathological, poisoned and poisoning, emperical and theoretical, and of opinions - a CHAOS. A dilemma - of students, beginners and practitioners failures.